2021
DOI: 10.1007/s13318-021-00700-5
|View full text |Cite
|
Sign up to set email alerts
|

The Challenging Pharmacokinetics of Mitotane: An Old Drug in Need of New Packaging

Abstract: Adrenocortical carcinoma (ACC) is a malignant tumor originating from the adrenal gland cortex with a heterogeneous but overall dismal prognosis in advanced stages. For more than 50 years, mitotane has remained a cornerstone for the treatment of ACC as adjuvant and palliative therapy. It has a very poor aqueous solubility of 0.1 mg/l and high partition coefficient in octanol/water (log P) value of 6. The commercially available dosage form is 500 mg tablets (Lysodren ® ). Even at doses up to 6 g/day (12 tablets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 139 publications
1
16
0
Order By: Relevance
“…It was recommended that mitotane treatment starts at a low dose and gradually increases to the maximum tolerated dose, and the daily dose should not exceed 18 g/day to avoid toxicity ( 36 ). However, it was found that mitotane daily dose was not related to clinically relevant changes in the blood mitotane level in our study, even if the difference in the blood mitotane concentration was statistically significant, which is consistent with previous results ( 18 ). In addition, we found no associations of age, weight, height, age of ACC diagnosis, and treatment time initial date with blood mitotane concentrations and no drug interaction between mitotane and inhibitors of CYP enzymes or antacids.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was recommended that mitotane treatment starts at a low dose and gradually increases to the maximum tolerated dose, and the daily dose should not exceed 18 g/day to avoid toxicity ( 36 ). However, it was found that mitotane daily dose was not related to clinically relevant changes in the blood mitotane level in our study, even if the difference in the blood mitotane concentration was statistically significant, which is consistent with previous results ( 18 ). In addition, we found no associations of age, weight, height, age of ACC diagnosis, and treatment time initial date with blood mitotane concentrations and no drug interaction between mitotane and inhibitors of CYP enzymes or antacids.…”
Section: Discussionsupporting
confidence: 93%
“…According to previous studies, cumulative dose on mitotane concentration is still controversial. The results of a small prospective and multicenter study involving 40 ACC patients, grouped to a low-dose or high-dose mitotane regimen, showed that, despite there being a difference in the average cumulative dose between the two groups, the median maximum plasma concentrations were not significantly different ( 18 ). Other literature confirmed a significant correlation of the cumulative dose of mitotane and the highest plasma mitotane trough level ( 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitotane treatment is started as soon as possible after surgery [ 5 ] with a low-dose (3 g/day after 12 days) or high-dose (3 g/day after 2 days, 6 g/day after 12 days) regimen, achieving similar plasma levels and demonstrating similar onset of adverse events [ 15 ]. Some patients do not achieve the therapeutic plasma concentration of 14–20 mg/L in the follow-up, even at doses up to 6–7 g/day (12–14 tablets in divided doses), due to poor water solubility, the large volume of distribution, the onset of adverse effects and inter/intra-individual variability [ 16 ]. Moreover, it has been found that 40% of unchanged mitotane could be detected in the feces 12 h after an oral intake of a single 2 g mitotane dose in tablet form [ 17 ].…”
Section: Endocrine Treatment: Mitotane and Steroidogenesis Inhibitorsmentioning
confidence: 99%
“…Moreover, it has been found that 40% of unchanged mitotane could be detected in the feces 12 h after an oral intake of a single 2 g mitotane dose in tablet form [ 17 ]. The most common mitotane-induced side effects in patients with ACC are gastrointestinal disturbances, neurologic symptoms, leukopenia and hepatic disorder (liver failure is rare; however, asymptomatic increases in hepatic enzymes—in particular, gamma-GT—are common) [ 5 ], alone or combined: they represent a major limit to treatment adherence [ 15 , 16 , 17 ]. Novel oral (recrystallization from microemulsion, nanosuspension, liposomal) and injectable (micellar) formulations are currently being developed in order to improve the efficacy and tolerability of mitotane [ 16 ].…”
Section: Endocrine Treatment: Mitotane and Steroidogenesis Inhibitorsmentioning
confidence: 99%